Die Kluft des Nicht-Verstehen-Wollens: Ein Beitrag zur Pädagogik Martin Wagenscheins (mathematica didactica, 2003)
The three bisectors of a triangle meet in one point: A phenomenography of twounderstanding processes of this phenomenon based upon different modes of approach (‚analytical‘vs ‚holistic‘) is given. Both (and more such) approaches turn out to be important for those teachers, who are practising Wagenschein’s exemplaric way of teaching.